Synthesis, characterisation and biological activities of mixed-ligand copper(II) complexes containing saccharin as one of the ligands - Begum, Thahira (2005)
New mixed-ligand copper(II) saccharinate complexes of HNNS Schiff bases of Smethyldithiocarbazate, S-benzyldithiocarbazate, S-2-picolyldithiocarbazate and S-4- picolyldithiocarbazate were synthesized by reacting [Cu(sac)2(H2O)4].2H2O with the appropriate Schiff bases in water-ethanol-methanol mixtures. These complexes were characterized by elemental analysis, conductance, magnetic susceptibility, IR and electronic spectroscopic measurements. Magnetic and spectral results for the complexes support either a four or five-coordinate geometry in which the Schiff bases coordinate as NNS tridentate ligands and the saccharinate anion coordinates as a unidentate N-donor ligand. X-ray crystallographic structural analysis of the copper(II)saccharinate complex of S-methyl-β-N-(6-methylpyrid-2-yl)methylenedithiocarbazate shows that the complex has a distorted square-pyramidal structure in which the Schiff base is coordinated to the copper ion as a tridentate NNS chelating agent via the pyridine nitrogen atom, the azomethine nitrogen atom and the thiolate sulphur atom. The fourth and fifth coordination positions of the five-coordinate Cu(II) ion are occupied by the imino nitrogen of the saccharinate anion and oxygen atom of the aqua ligand. X-ray crystallographic structural analysis of the copper(II)saccharinate complex of S-benzyl-β- N-(2-acetylpyridyl)methylenedithiocarbazate shows that this complex has a distorted square-planar structure in which the Schiff base is also coordinated to the copper ion as a tridentate NNS chelating agent with the fourth coordination position of the fourcoordinate Cu(II) ion being occupied by the imino nitrogen of the saccharinate anion. The complexes have been evaluated for their biological activities against seven pathogenic microbials and three cancer cell lines, HL-60 (Human myeloid leukemic cells), MCF-7 (Human breast carcinoma cells with positive estrogen receptor) and Caov-3 (Human ovarian adenocarcinoma cancer cells). Most of the complexes exhibit marked cytotoxicity against the cell lines and display moderate activity against pathogenic bacteria and fungi.